The Role of Reverse Logistics in a Circular Economy Conditions in the European Union - Mihova, Lilyana (Research Papers, 2020)
In the context of sustainable development, the circular economy and reverse logistics are two concepts that are becoming increasingly popular and whose relationship is not so obvious. The purpose of this article is to show the relationship between them and to clarify the essence of the two concepts. In order to achieve this, a literature review has been made and data on the degree of implementation of environmental practices in the packaging, consumption and recycling of logistics services providers in Bulgaria derived from an empirical study has been presented. As a result of the study, basic concepts were developed and an analysis of the research gaps was made. The review might be useful for scientists, researchers and practitioners for better understanding of reverse logistics in green economy conditions and guidance for future research.
Keywords: Sustainable development; Reverse logistics; Circular economy; Green economy